Tissue‐Engineered Vascular Grafts Created From Human Induced Pluripotent Stem Cells. (5th November 2014) - Sundaram, Sumati; One, Jennifer; Siewert, Joshua; Teodosescu, Stephan; Zhao, Liping; Dimitrievska, Sashka; Qian, Hong; Huang, Angela H.; Niklason, Laura
Abstract : Tissue‐engineered vascular grafts were created using human induced pluripotent stem (hiPS) cells. The results provide significant insight into the utility of hiPS cells for vascular graft generation and pave the way for creating personalized, patient‐specific vascular grafts for surgical applications, as well as for creating experimental models of vascular development and disease. Abstract : The utility of human induced pluripotent stem cells (hiPSCs) to create tissue‐engineered vascular grafts was evaluated in this study. hiPSC lines were first induced into a mesenchymal lineage via a neural crest intermediate using a serum‐free, chemically defined differentiation scheme. Derived cells exhibited commonly known mesenchymal markers (CD90, CD105, and CD73 and negative marker CD45) and were shown to differentiate into several mesenchymal lineages (osteogenic, chondrogenic, and adipogenic). Functional vascular grafts were then engineered by culturing hiPSC‐derived mesenchymal progenitor cells in a pulsatile bioreactor system over 8 weeks to induce smooth muscle cell differentiation and collagenous matrix generation. Histological analyses confirmed layers of calponin‐positive smooth muscle cells in a collagen‐rich matrix. Mechanical tests revealed that grafts had an average burst pressure of 700 mmHg, which is approximately half that of native veins. Additionally, studies revealed that karyotypically normal mesenchymal stem cell clones led to generation of grafts with predicted features of engineered vascular grafts, whereas derived clones having chromosomal abnormalities generated calcified vessel constructs, possibly because of cell apoptosis during culture. Overall, these results provide significant insight into the utility of hiPS cells for vascular graft generation. They pave the way for creating personalized, patient‐specific vascular grafts for surgical applications, as well as for creating experimental models of vascular development and disease.